Would Consumers Pay More for Nongenetically Modified Menu Items? An Examination of Factors Influencing Diners’ Behavioral Intentions - Lu, L.; Gursoy, Dogan (Routledge, 2017)
The purpose of this study is to examine diners’ purchase intentions and willingness to pay a premium for nongenetically modified (GM) menu items at restaurants. A theoretical model was developed based on the premises of the theory of planned behavior. The magnitude and significance of the hypothesized interrelationships among the constructs included in the model were tested utilizing a structural modeling approach. Results indicate that 75% of the participants are willing to pay a premium (13% more) for non-GM menu items at restaurants. Personality trait (consideration of future consequences) and social trust significantly affect consumers’ attitudes towards GM foods. Diners’ attitudes towards GM foods are found to be the primary determinant of purchase intentions of non-GM menu items, followed by subjective norms and perceived behavioral control. Purchase intentions of non-GM menu items also exert a substantial impact on consumers’ willingness to pay a premium. Theoretical contributions, managerial implications, and limitations are addressed.